2015
DOI: 10.1002/ece3.1799
|View full text |Cite
|
Sign up to set email alerts
|

Specialists in ancient trees are more affected by climate than generalists

Abstract: Ancient trees are considered one of the most important habitats for biodiversity in Europe and North America. They support exceptional numbers of specialized species, including a range of rare and endangered wood‐living insects. In this study, we use a dataset of 105 sites spanning a climatic gradient along the oak range of Norway and Sweden to investigate the importance of temperature and precipitation on beetle species richness in ancient, hollow oak trees. We expected that increased summer temperature would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Based on the assumption that climate and land use conditions have negatively affected species inhabiting mountain habitats (Arlettaz et al, ; Brambilla et al, ; Herrando et al, ; Ims & Hender, ; Lehikoinen et al, ), we hypothesize that mountain bird species, in general, are declining in numbers. Second, we hypothesize that this decline would be stronger in mountain specialists that only occur in mountain areas in our study sites, whereas mountain generalists, which also can be found at lower elevations, are doing better because of generally higher ecological flexibility (Davey, Chamberlein, Newson, Noble, & Johnston, ; Davey, Devictor, Jonzén, Lindström, & Smith, ; Gough et al, ). Third, we predict that population trends of mountain species can be influenced by the migration status of species.…”
Section: Introductionmentioning
confidence: 94%
“…Based on the assumption that climate and land use conditions have negatively affected species inhabiting mountain habitats (Arlettaz et al, ; Brambilla et al, ; Herrando et al, ; Ims & Hender, ; Lehikoinen et al, ), we hypothesize that mountain bird species, in general, are declining in numbers. Second, we hypothesize that this decline would be stronger in mountain specialists that only occur in mountain areas in our study sites, whereas mountain generalists, which also can be found at lower elevations, are doing better because of generally higher ecological flexibility (Davey, Chamberlein, Newson, Noble, & Johnston, ; Davey, Devictor, Jonzén, Lindström, & Smith, ; Gough et al, ). Third, we predict that population trends of mountain species can be influenced by the migration status of species.…”
Section: Introductionmentioning
confidence: 94%
“…For instance, species may shift their distributions by migrating to unaffected or climatically similar areas (Parmesan andYohe 2003, Moritz et al 2008). While this research provides valuable insight into the effects of global warming on generalist consumers, the impacts of climate change on dietary specialists are not as readily apparent (Gough et al 2015). Regardless of the mechanism, climate change research has often focused on the responses of single species to changes in global climate.…”
Section: Introductionmentioning
confidence: 99%
“…Several variables—climate, area of old forest, and volume—also change systematically along this gradient (see Table ). Their influences cannot be clearly separated from those of historical logging, but if the observed species’ responses were due solely to climate, we would expect highest species richness along the coast where temperatures were high and precipitation low (Gough et al., ; Müller et al., ). This is opposite to the observed pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Gough et al. () found that oak specialists responded negatively to summer precipitation and positively to increased summer temperatures when studying a 700‐km climatic gradient across Sweden and Norway. Our inland sites should therefore be climatically less favorable.…”
Section: Discussionmentioning
confidence: 99%